Centering Subjectivities: Theoretical Considerations for Practice With Women in Forced Migration. Issue 3 (August 2018) - Wachter, Karin; Snyder, Susanna
Postcolonial feminist and African diaspora theories provide lenses through which to consider the impacts of forced migration on the internal and relational lives of women—aspects of experience less visible in policy, practice, and scholarship. Policy, practice, and research contribute to the framing of "refugees" as a static category of people irrespective of complex histories, geopolitical origins, and fluid identities impacted by structural forces. They can thus deny the subjective possibilities of women through the construction of identities that informs who refugees are and who they are expected to become. These overarching trends reflected in policy and practice have particular implications for women whose internal and relational processes remain to a large extent invisible. Drawing from postcolonial feminist and African diaspora theories, this article suggests that a practice of centering the subjectivities of women in forced migration may enhance the work of researchers and practitioners.